Calculation of sound pressure level of marine propeller in low frequency. Issue 1 (March 2018) - Gorji, Mohsen; Ghassemi, Hassan; Mohamadi, Jalal
The research performed in this paper is carried out to calculate the sound pressure level of the marine propeller by Reynolds-Averaged Navier–Stokes solver in low frequencies band. Noise is generated by the induced trailing vortex wake and induced pressure pulses. The two-step Fflowcs Williams and Hawkings equations are used to calculate hydrodynamic pressure and its performance as well as sound pressure level at various points around the propeller. The directivity patterns of this propeller and accurate explanation of component propeller noise are discussed. Comparison of the numerical results shows good agreement with the experimental data.